Analisis Perbedaan Tekanan Suara di Mikrofon Internal dengan Mikrofon Eksternal pada Aplikasi Soundmeter berbasis Ponsel - Muhammad Agni Catur Bhakti; Wandy Wandy (Jurnal Teknologi, 2021)
Mobile phones and tablets installed with a soundmeter application can be used as an alternative for recording noise pollution to support Occupational Health and Safety (OHS). Mobile and tablet applications that have been calibrated with a soundmeter has the ability to record sound pressure which could be a solution for data recording. An external microphone can be attached to mobile phones and tablets to improve the quality of recorded data from sound sources. This research aims to analyze and determine the differences between the sound captured by internal and external microphones, and then compared them with results from a soundmeter device. This research was conducted using quantitative methods with primary data being analyzed descriptively. It was concluded from this research that there were significant increments in sound pressure using external microphones compared to internal microphones, with increment average using external microphone of 6.11 dBA on mobile phone, and 8.09 dbA on tablet.